2021
DOI: 10.32607/actanaturae.11375
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Snake Toxins: Cardiotoxicity and Cardioprotection

Abstract: Snake venoms, as complex mixtures of peptides and proteins, affect various vital systems of the organism. One of the main targets of the toxic components from snake venoms is the cardiovascular system. Venom proteins and peptides can act in different ways, exhibiting either cardiotoxic or cardioprotective effects. The principal classes of these compounds are cobra cardiotoxins, phospholipases A2, and natriuretic, as well as bradykinin-potentiating peptides. There is another group of proteins capable of enhanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 92 publications
0
20
0
Order By: Relevance
“…Here, we have shown that venom of Bothrops lanceolatus deteriorates oxidative phosphorylation capacity in human cardiac preparation. Further experiments using contracting isolated human right atrial trabeculae are warranted to demonstrate that PLOS NEGLECTED TROPICAL DISEASES such oxidative phosphorylation deficits may be associated with cardiac contractile dysfunction, which can occur in pitviper snake envenoming [20,21]. Secondly, we found that venom of Bothrops lanceolatus impaired mitochondrial membrane permeability, which was evaluated indirectly by measuring reduction of exogenous cytochrome c (Cyt c) in the medium of cardiac fiber preparation.…”
Section: Discussionmentioning
confidence: 87%
“…Here, we have shown that venom of Bothrops lanceolatus deteriorates oxidative phosphorylation capacity in human cardiac preparation. Further experiments using contracting isolated human right atrial trabeculae are warranted to demonstrate that PLOS NEGLECTED TROPICAL DISEASES such oxidative phosphorylation deficits may be associated with cardiac contractile dysfunction, which can occur in pitviper snake envenoming [20,21]. Secondly, we found that venom of Bothrops lanceolatus impaired mitochondrial membrane permeability, which was evaluated indirectly by measuring reduction of exogenous cytochrome c (Cyt c) in the medium of cardiac fiber preparation.…”
Section: Discussionmentioning
confidence: 87%
“…For SVs, numerous bioassays are currently used for different specific components. In fact, SVs induce a wide spectrum of effects once injected in prey, since they target several organ systems: namely, the nervous and the cardiovascular systems [59]. Different bioassays are developed for the isolation of cardiotoxic and neurotoxic components.…”
Section: Bioassay-guided Fractionationmentioning
confidence: 99%
“…Different bioassays are developed for the isolation of cardiotoxic and neurotoxic components. Since SV cardiotoxic components are known to have effects on the cardiac muscle or vascular smooth muscle [59], several bioassays might be used for the isolation of cardiotoxic components.…”
Section: Bioassay-guided Fractionationmentioning
confidence: 99%
“…CTs are cobra venom membrane-active cationic proteins that have been successfully used to probe the structure and functions of biological and model membranes [ 19 , 20 , 21 ]. CTs are known for affecting the heart contractility through an induction of changes in the Na + /Ca 2+ transmembrane exchange and for altering the ATP synthase activity through triggering changes in the lipid phase polymorphism of mitochondrial membranes [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…CTs are cobra venom membrane-active cationic proteins that have been successfully used to probe the structure and functions of biological and model membranes [ 19 , 20 , 21 ]. CTs are known for affecting the heart contractility through an induction of changes in the Na + /Ca 2+ transmembrane exchange and for altering the ATP synthase activity through triggering changes in the lipid phase polymorphism of mitochondrial membranes [ 19 , 20 , 21 , 22 , 23 ]. It has been suggested that CTs have evolved from the body’s native membrane-active proteins which modulate the activities of membrane-embedded proteins in the plasma membrane and the membranes of organelles via an induction of changes in the morphology and dynamics of the membrane lipid phase [ 24 ].…”
Section: Introductionmentioning
confidence: 99%